COMPETITION EXERCISES AND THEIR EFFECT ON THE PERCENTAGE OF BLOOD SATURATION WITH OXYGEN AND THE ACCURACY OF SKILL PERFORMANCE AMONG TENNIS PLAYERS - Asst. Lect Ayman Abde Kariz; Prof .Dr Ammar Jassim Muslim; Prof .Dr Makki Jabbar Almajdy (Proximus Journal Publishing, 2025)
The research aims to identify the effect of competition exercises on the percentage of blood oxygen saturation and the accuracy of skill performance among tennis players. The experimental method was used and the research community was represented by the players of the Tennis Federation Club in Maysan, which numbered (10) players. The researchers used pre- and post-tests and measurements that are consistent with the requirements of the research. The results of the study indicated the following: Competition exercises affected the percentage of blood oxygen saturation and the accuracy of skill performance among tennis players effectively among the members of the experimental group
Keywords: competition exercises; blood oxygen saturation